A EU-Taiwan trade accord from EU member states perspective: Rebalancing regional trade - Michal Krol; Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2012)
Following an FTA with Korea, the EU now takes up the ambitious task of negotiating an FTA with Japan. Inarguably, "big" FTAs are the way forward in the search for growth, but in parallel, the EU should aim to diversify its regional outreach to rebalance trade accounts. In this sense, Taiwan has the potential to "repair" some of the effects from other Asian FTAs on EU's sensitive areas and distribute the gains beyond traditional export-driven Member States. Despite its relatively small size, Taiwan can also spur EU growth provided by indirect market access to China. This policy brief looks at the potential gains of a EU-Taiwan trade accord from an individual Member State perspective. It concludes that the expected benefits from such agreement would be equally distributed across key EU Member States - including sectors and countries that are deemed to be on the paying side of EU's FTAs, such as agriculture or cars. Both France and the UK can move from a current motor vehicle deficit to a surplus by doubling its export and improving their surpluses on agricultural products by exteuro200- exteuro400 million each. Individual Member State can increase their overall export by at least 50% on sectors where its primary specialization lies - Germany on machinery and cars, France on miscellaneous goods, agriculture and services, whereas the UK foremost on services.
Keywords: 330; Handelsabkommen; Freihandelszone; EU-Staaten; Taiwan